The Influence of Strategic Orientation, Adaptive Marketing Capability and Sustainable Competitive Advantage on Business Performance of Multi-Level Marketing Companies in Malaysia - Lee, Siew Keong (2023)
Many multi-level marketing (MLM) companies in Malaysia have failed to maintain sustainability and experienced a high rate of attrition due to their inability to sustain. Despite all support from the Malaysia Ministry of Domestic Trade and Consumer Affairs and Direct Selling Association Malaysia, the level of sustainability of MLM firms in Malaysia is still low. This study investigates the impact of strategic orientations (market, learning, intellectual capital, technology) on sustainable competitive advantage (SCA) through adaptive marketing capabilities (AMC) among Malaysian MLM companies. A quantitative approach is employed in this study. The founders, CEOs, COOs, CMOs, General Managers, or equivalent positions of MLM firms are surveyed to gather data. A total of one hundred and two responses were collected and subsequently subjected to analysis. The SmartPLS software was employed to assess the research models and test the proposed hypotheses. The empirical findings indicate robust evidence for the model’s explanatory power, which shows that it accounts for 71 percent of the variance in AMC and 77.3% in SCA. Market orientation has a weak relationship with SCA but has a positive relationship with SCA through AMC’s full mediating effect. No mediation is evident between learning orientation and SCA; instead, a direct inverse connection between learning orientation and SCA is observed. Furthermore, technology orientation exerts a direct positive influence on SCA. AMC serves as a partial mediator, whereas intellectual capital does not exhibit any mediating effect through AMC but rather maintains a direct positive association with SCA. In combination, market, learning, intellectual capital, and technology orientation possess similar explanatory power in accounting for the variability in AMC. As a result, when these factors are combined, they contribute more to enhancing AMC and SCA. This study has highlighted the understanding and challenges of applying strategic orientation-capabilities-SCA relationship link concepts to the literature of the MLM sector and significantly contribute to the field of strategic marketing by advancing knowledge and understanding in areas such as strategic orientation, AMC and SCA. The ability of Malaysia’s MLM firms to address the obstacles and effectively utilize their resources and capabilities to improve firm capability hinges on the management’s competence in creating and deploying a suitable blend of essential resources.